A tradable employment quota - Metin Akyol; Michael Neugart; Stefan Pichler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Discrimination of women in the labor market requires appropriate policy interventions. Affirmative action policies typically advocate the introduction of an employment quota uniformly applied to all firms. In a heterogeneous labor market such a policy may yield avoidable welfare losses. We propose a tradable employment quota showing its effects on wages, employment, and welfare in a labor market with search frictions and taste discrimination. A tradable employment quota appears to be a viable alternative yielding superior labor market outcomes.
Keywords: J71; J78; C63; 330